Care Watch / Murni Umairah Mohd Yusoff … [et al.] - Mohd Yusoff, Murni Umairah; Marzuki, Musqfirah; Zamri, Nur Zaheeda Syafiqa; Jamaluddin, Nurina Hadhifah; Muhamad Rozaidi, Siti Nur Soleha; Muhamad Hanapiyah, Zulkefli (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Care Watch is a new product concept based on Smartwatches that are already on the market. Care Watch aims to make it easier for people with disabilities (OKU) to move from one area to another without danger. Among the functions of this Care Watch are vibrations, sounds and notifications when there is danger within a certain distance. Additionally, this watch can track the user. So, with this Care Watch, users can know where a person (OKU) is. Furthermore, parents can keep an eye on their children. These functions are very important to ensure the safety of users (OKU) is always guaranteed. Our purpose in making this Care Watch is to please some caregivers to take care of children or family members with disabilities. Among the disabled people who can use this product are people with disabilities (OKU) who are blind, autistic, deaf and many more. This clock can not only be used by people with disabilities (OKU) but it can be used by children, students and all walks of life.